English-Based Threads Accounts as Informal Learning Media for EFL Learners - Melisa Melisa; Maslathif Dwi Purnomo; Sholihatul Hamidah Daulay (FKIP - Universitas Riau, 2026)
This study examines the role of English-based Threads accounts as informal learning platforms for English as a Foreign Language (EFL) learners. The objective is to identify the categories of English-learning content disseminated, analyze patterns of learner interaction and engagement, and assess the educational values felt by learners utilizing Threads as an informal learning platform. This study used a qualitative phenomenological research approach to explore the lived experiences of content authors and learners, reflecting the increasing interest in informal language learning facilitated by social media. Data were gathered by systematic content observation, document analysis of posts and comments, and comprehensive interviews with four purposefully selected English-learning Threads accounts: @englishwithzah, @englishwithwahyu, @englishwithfaqih, and @bbyadthma. Analysis of 175 postings and 2,847 comments was conducted from October to November 2025. The results indicate four primary content categories: educational, motivational, interactive, and multimodal content. Learner engagement manifested through five patterns: public interaction, creator-learner discussion, peer learning, and off-platform speaking practice. Learners recognized various educational benefits, including accessibility, microlearning, emotional support, learner autonomy, and a low-anxiety learning atmosphere, while also illustrating the importance of critical and active participation. This study emphasizes the potential of Threads as an informal learning environment for EFL learners.